2019
DOI: 10.3390/ijerph16234854
|View full text |Cite
|
Sign up to set email alerts
|

Access to Services in Rural Areas from the Point of View of Older Population—A Case Study in Finland

Abstract: Independence and having control over one’s own life are important factors for residential satisfaction. In rural areas, the mobility of people is based on owning a private car, due to the lack of public transport. Furthermore, planning in rural municipalities is highly car oriented. Small municipalities with shrinking and aging populations have many challenges to ensure access to services for their residents. This paper focuses on a case study of a small municipality with less than 2000 inhabitants. The object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
0
16
0
2
Order By: Relevance
“…The low density and scattered housing fabric of small towns and villages, typical of these territories, make it difficult to operate traditional public transport services, which can hardly be efficient with such a low and dispersed demand [9][10][11]39,40]. Therefore, these territories are highly car-dependent, and the groups of users that are most affected by the lack of accessibility are those who, due to age, economic, or cultural barriers, do not have access to cars [7,8,12,13]. The population groups that are already vulnerable in themselves are therefore those most affected by the lack of accessibility, and this applies both within rural areas and in the connection with the nearest urban centers where basic services are located [41][42][43].…”
Section: Accessibility Challenges In Rural Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…The low density and scattered housing fabric of small towns and villages, typical of these territories, make it difficult to operate traditional public transport services, which can hardly be efficient with such a low and dispersed demand [9][10][11]39,40]. Therefore, these territories are highly car-dependent, and the groups of users that are most affected by the lack of accessibility are those who, due to age, economic, or cultural barriers, do not have access to cars [7,8,12,13]. The population groups that are already vulnerable in themselves are therefore those most affected by the lack of accessibility, and this applies both within rural areas and in the connection with the nearest urban centers where basic services are located [41][42][43].…”
Section: Accessibility Challenges In Rural Areasmentioning
confidence: 99%
“…Those marginalization processes are at the same time the causes and consequences of scarce accessibility, which in rural territories is particularly challenging [6] and undermines the livability of rural communities. Moreover, due to their spatial and socio-economic conditions, rural territories are highly car-dependent [7,8]; traditional public transport services can hardly be efficient under such conditions, and those who are most affected are people who have limited access to car use [7][8][9][10][11][12][13]. Therefore, providing and supporting alternative forms of transport in rural areas is primarily aimed at counteracting transport exclusion.…”
Section: Introductionmentioning
confidence: 99%
“…In Pertunmaa, residents used local services in the commercial center 10 km from the municipal center and in several smaller towns within 60 km. Only a few persons reported using only services in their municipal centre [16]. The results of the survey in Keuruu showed that the amount of online shopping was also significant (Figure 4).…”
Section: Access To Servicesmentioning
confidence: 95%
“…The more aggravated these inconveniences become in using public transportation, the more Sustainability 2021, 13, 5574 2 of 19 personal vehicles are being used. In this regard, research related to automobile dependence on the outskirts [4][5][6] and sustainable rural access [7][8][9][10] was recently conducted. This automobile dependence leads to demand that exceeds the limited capacity of roads, causing severe traffic congestions.…”
Section: Introductionmentioning
confidence: 99%